Foraging behaviour of birds in an arid sand-dune scrubland in Argentina - Blendinger, Pedro Gerardo (2005)
Studies of the foraging behaviour of birds allow exploration of the mechanisms that structure species assemblages. The major objective of this study was to describe relationships among various components of foraging behaviour and whether changes in those relationships reflected seasonal changes in assemblage structure of birds from an arid scrubland of the Monte Desert, Argentina. Foraging behaviour was described in terms of attack manoeuvres, food substrate (i.e. substrate from which food taken), foraging site (i.e. the substrate and height where birds foraged), and plant species used. Between-species differences in these three components of foraging behaviour were interrelated, the association being strongest between foraging sites and food substrates. During the non-breeding season, foraging sites and food substrates differentiated species. The most important changes between seasons were related to the arrival in summer of aerial-foraging tyrant flycatchers, a functional group absent during the non-breeding season. Foraging sites explained most of the differences among species groups, suggesting that habitat heterogeneity and structural complexity of vegetation are important environmental variables that determine the avian assemblage structure. Moreover, temporal changes in food availability, mediated by strong seasonality in climate, were important factors that were correlated with compositional and structural variability in functional groups of birds (i.e. granivores-insectivores, surface insectivores and aerial insectivores).